Effect of anti-Müllerian hormone in hypothalamic Kiss-1- and GnRH-producing cell models. (2nd September 2021) - Oride, Aki; Kanasaki, Haruhiko; Tumurbaatar, Tuvshintugs; Tumurgan, Zolzaya; Okada, Hiroe; Kyo, Satoru
Abstract: Purpose: Anti-Müllerian hormone (AMH) is one of the local factors involved in follicle development. In addition, AMH and its receptor are broadly expressed throughout the body. In this study, we examined how AMH modifies gene expression of Kiss-1 and GnRH. Materials and methods: mHypoA-50 and mHypoA-55 cells were originated from the hypothalamic anteroventral periventricular nucleus (AVPV) and arcuate nucleus (ARC), respectively, and these cells are known as Kiss-1 (which encodes kisspeptin) expressing cell models. These cells also express gonadotropin-releasing hormone (GnRH) genes. Our experiments were performed useing these cell models. Results: Both mHypoA-50 and mHypoA-55 hypothalamic cells expressed AMH and AMH receptor type 2 (AMHR2). Exogenous AMH failed to alter the expression levels of the Kiss-1 gene in both cell models but significantly increased GnRH gene expression by 1.73 ± 0.2-fold at 100 pM in mHypoA-50 AVPV cells and by 1.74 ± 0.17-fold at 1 nM in mHypoA-55 ARC cells. AMH also augmented GnRH protein expression in both cell models. Similar to the phenomenon observed in the hypothalamic cell lines, 100 pM AMH significantly increased GnRH, but not Kiss-1, mRNA expression in primary cultures of fetal rat brain cells. Kisspeptin-10 (KP10) increased Kiss-1 gene expression in mHypoA-55 ARC cells but this was blocked by AMH. AMH did not alter the expression of the kisspeptin receptor (Kiss1R) or that of neurokinin B or dynorphin A in mHypoA-55 ARC cells. Conclusions: It was demonstrated that AMH participates in hypothalamic-pituitary-gonadal axis control by stimulating GnRH expression. In addition, AMH might be a potent repressor of Kiss-1 gene expression induced by KP10.